(3bQGAIs - (3YHO GdQMef Jbj GdOjf Hf CHj GdNjQ JGL GdOjf YHO GdZfj Hf eMeO GdMQjQj Hf GdYbGO GdMfHdjs ((3XGgQ GdbGgQI GdeYRHI s)
(3ChdgG (B:s
(3CMeO Gddg GdPi QaY GdYdeGA hHYO abO bQC Ydi GdYHO GdabjQ Edi Gddg JYGdi HGdbQGAGJ GdSHY eeG JVefg hMhGg cJGH GdJjSjQ ddOGfi s
(3BNQgG (B:s
(3hCSGfOi ai Pdc ePchQ ai cJGH TjNfG GdYdGeI TeS GdOjf eMeO GdLRQi ai GdbQGAGI GdYTQ aef CQGO Gdhbha Ydi Pdc aYdjg HGdcJGH GdePchQ GdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B11s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3eUOQ GbJfGA GdCUd (B:s
(3eOQSI GdMLjGJ (B_(3GdehUd (B(117) s
Keywords: (3GdeLGejYs